The Potential Role of Trained Immunity in Autoimmune and Autoinflammatory Disorders - Arts, Rob J. W.; Joosten, Leo A. B.; Netea, Mihai G. (Frontiers in Immunology, 2018)
During induction of trained immunity, monocytes and macrophages undergo a functional and transcriptional reprogramming towards increased activation. Important rewiring of cellular metabolism of the myeloid cells takes place during induction of trained immunity, including a shift towards glycolysis induced through the mTOR pathway, as well as glutaminolysis and cholesterol synthesis. Subsequently, this leads to modulation of the function of epigenetic enzymes, resulting in important changes in chromatin architecture that enables increased gene transcription. However, in addition to the beneficial effects of trained immunity as a host defense mechanism, we hypothesize that trained immunity also plays a deleterious role in the induction and/or maintenance of autoimmune and autoinflammatory diseases if inappropriately activated.